A decade of delusions from speculative contagion to the great recession - Martin, Frank K. (Wiley, 2011)
"The proven strategies rational investors require for success in an irrational market When the dot-com and real estate bubbles of the 1990s and 2000s burst, few were spared the financial fallout. So, how did an investment advisory firm located in Elkhart, Indiana--one of the cities hit hardest by the economic downturns--not only survive, but also thrive during the highly contagious speculative pandemics. By remaining rational. In A Decade of Delusions: From Speculative Contagion to the Great Recession, Frank Martin founder of Elkhart, Indiana's Martin Capital Management offers a riveting and real-time insider's look at the two bubbles, and reflects on how investors can remain rational even when markets are anything but. Outlines strategies the average investor can use to wade through the endless news, information, and investment advice that bombards them Describes the epidemic of market speculation that gradually infects feverish investors Details how investors can spare themselves the emotional devastation and accompanying paralysis resulting from shocking financial losses Investors are still reeling from the instability in the market. A Decade of Delusions: From Speculative Contagion to the Great Recession provides the information investors need to achieve safety, liquidity, and yield"--